ANALISIS PENGETAHUAN DAN SIKAP SISWA SMP PEMBANGUNAN UNP TENTANG OBESITAS DAN OVERWEIGHT DENGAN PENYULUHAN GIZI MENGGUNAKAN MEDIA FLIPCHART - Zulferi Zulferi; Siti Syafita; Marni Handayani (Ensiklopedia of Journal, 2020)
The purpose of this study was to determine the effect of counseling with group discussion methods using flipchart media on knowledge and attitudes about overweight and obesity in class IX students in junior high schools. Pre-experiment research design with the One Group Pre-Post Test method. The research was conducted from February 2019 to April 2020. The respondents of class IX students who were overweight and obese numbered 32 people, a simple random sampling technique. Data were collected by interview using a questionnaire. Data were analyzed using Wilcoxon test. The results of the study are, there are significant differences in the level of knowledge and attitudes of students between before and after counseling the value of p = 0,000 (p ≤ 0.05). It is hoped that other researchers will continue the extension research with group discussion using flipchart media. In addition, it is also hoped that there will be researchers who research extension with different methods and media that are more interesting to improve students' knowledge and attitudes.